New genus of gelechiid moths (Lepidoptera: Gelechiidae) from Borneo, and its four new species - Ponomarenko, Margarita G.; Omelko, Michail M.; Omelko, Natalia V. (Zootaxa, 2021)
Tawaya gen. n. and its four new species (T. flaventia sp. n., T. rutila sp. n., T. luteola sp. n. and T. armeniaca sp. n.) are described from Borneo. A key to the described species is provided. The taxonomic position of a new genus within the subfamily Dichomeridinae (Gelechiidae) is proposed based on a combination of molecular and morphological analyses.